2008
DOI: 10.1111/j.1471-0528.2008.02005.x
|View full text |Cite
|
Sign up to set email alerts
|

Fetal mesenchymal stem cells: isolation, properties and potential use in perinatology and regenerative medicine

Abstract: The fetus is a source of nonembryonic stem cells (SC), with potential applications in perinatal medicine. Cells derived from the placenta, membranes, amniotic fluid or fetal tissues are higher in number, expansion potential and differentiation abilities compared with SC from adult tissues. Although some obstacles keep SC biology at distance from clinical application, the feasibility of using (homologous) SC for tissue engineering for the fetus with a congenital birth defect has been demonstrated. Also, other p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 59 publications
(65 reference statements)
1
72
0
3
Order By: Relevance
“…From amnion tissue both epithelial and stromal amnion cells can be obtained, representing an interesting cell types to be tested in horse for differentiation processes other than the mesenchymal lineage. Recently placenta-derived stem cells have attracted attention as a novel cell source for cell transplantation (Gucciardo et al 2009) as, among other features; the harvest of such cells does not require any invasive treatment. Interestingly, being fetal cells, amnion-derived cells could offer a number of therapeutic advantages over adult stem cells as they can differentiate in vitro into diverse cells types, have low immunogenicity and anti-inflammatory function, making them well suited for cell replacement therapy (Parolini et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…From amnion tissue both epithelial and stromal amnion cells can be obtained, representing an interesting cell types to be tested in horse for differentiation processes other than the mesenchymal lineage. Recently placenta-derived stem cells have attracted attention as a novel cell source for cell transplantation (Gucciardo et al 2009) as, among other features; the harvest of such cells does not require any invasive treatment. Interestingly, being fetal cells, amnion-derived cells could offer a number of therapeutic advantages over adult stem cells as they can differentiate in vitro into diverse cells types, have low immunogenicity and anti-inflammatory function, making them well suited for cell replacement therapy (Parolini et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Adherent stromal cells with similar characteristics were subsequently isolated from other tissues such as adipose, dental pulp, muscle, liver and brain (Porada et al 2006;Huang et al 2009). They are also found in foetal and extraembryonic tissues, where they seem to possess greater proliferation capacity and differentiation potential than their adult counterparts Guillot et al 2007b;Pappa & Anagnou 2009 Gucciardo et al 2009), but express stromaassociated markers CD29 (b1-integrin), CD73 (SH3 and SH4), CD105 (SH2), CD44 (HCAM1), the early bone marrow progenitor cell marker CD90 (thy-1) and the extracellular matrix proteins vimentin, laminin and fibronectin (Guillot et al 2006(Guillot et al , 2007a. Contrary to adult bone marrow MSCs, first-trimester foetal blood, liver and bone marrow MSCs express baseline levels of the pluripotency stem cell markers Oct-4, Nanog, Rex-1, SSEA-3, SSEA-4, Tra-1-60 and Tra-1-81 (Guillot et al 2007b;Zhang et al 2009).…”
Section: Foetal Tissuesmentioning
confidence: 99%
“…Advantages of amnion over other sources for stem cells included abundant availability, ethically non-objectionable and non-invasive source. The MSCs from AM (AMSCs) are thought to be in an intermediate stage between embryonic stem cells and lineage-restricted adult stem cells (In't Anker et al 2004;De Coppi et al 2007;Gucciardo et al 2009). Recently, Yamahara et al (2014) reported that mesenchymal stem cells isolated from human amniotic tissue have an angiogenesis potential.…”
Section: Introductionmentioning
confidence: 99%